Reflections on the failed same-sex marriage referendum held in Romania - López Rubio, Daniel (EUNOMÍA. Revista en Cultura de la Legalidad, 2019)
In October 2018, Romania held a referendum on the ban of same-sex marriages, which indeed had got the support of a wide majority in the Chamber of Deputies and the Senate. The call for this referendum generated the usual criticism towards the institution of the referendum itself, that points out its inconvenience when it comes to dealing with issues regarding minorities’ rights. Drawing on the Romanian experience, this paper analyses that criticism by going through the contradictions and questions that arise when it is vaguely expressed. The purpose is to compare the advantages of a parliamentary forum and referendums as decision-making tools and to insist in the need of clarifying the specific kind of popular consultation that is to be used. Finally, the writer argues in favor of preserving referendums as decisive means in the process of constitutional reform, stressing however the drawbacks that may eventually arise in case of a judicial review.